2020
DOI: 10.1039/c9ew01048c
|View full text |Cite
|
Sign up to set email alerts
|

Integration of aerobic granulation and UV/H2O2 processes in a continuous flow system for the degradation of sulfolane in contaminated water

Abstract: Aerobic granulation and UV/H2O2 in a continuous flow-through reactor can effectively degrade emerging contaminates, such as sulfolane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Figure 3 displays the 16 most abundant genera detected in the 8-chamber PFR as compared with their abundance in the AS control samples. Of these genera, 8 have been previously reported in granular sludge reactors and/or are composed of filamentous organisms and/or producers of EPS: Flavobacterium , Hydrogenophaga , Thiothrix , Pseudomonas , Acidovorax , Cloacibacterium , Acinetobacter , and Aeromonas [ 6 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 47 , 48 ]. In their review of the bacterial composition of aerobic granules, Xia et al [ 6 ] indicated the prevalence of several of the most abundant genera identified in our study, including Flavobacterium , Thiothrix , Acinetobacter , Acidovorax , Hydrogenophaga , and Sphaerotilus .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 displays the 16 most abundant genera detected in the 8-chamber PFR as compared with their abundance in the AS control samples. Of these genera, 8 have been previously reported in granular sludge reactors and/or are composed of filamentous organisms and/or producers of EPS: Flavobacterium , Hydrogenophaga , Thiothrix , Pseudomonas , Acidovorax , Cloacibacterium , Acinetobacter , and Aeromonas [ 6 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 47 , 48 ]. In their review of the bacterial composition of aerobic granules, Xia et al [ 6 ] indicated the prevalence of several of the most abundant genera identified in our study, including Flavobacterium , Thiothrix , Acinetobacter , Acidovorax , Hydrogenophaga , and Sphaerotilus .…”
Section: Resultsmentioning
confidence: 99%
“…Biofilm formation is a complex process that is regulated by bacterial signal transduction pathways designed to detect environmental stressors like nutrient deprivation [ 13 , 14 ]. As such, key groups of bacteria capable of synthesizing EPS for biofilm formation have been observed in higher abundance in SBR systems with successful aerobic granulation [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In a pilot study, we recently demonstrated that aerobic granulation can be implemented in a simulated plug flow reactor (PFR) using real domestic wastewater [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Heydari et al used ethyl acetate for water sample extraction, although no information about the extraction performance was provided in their publication [26]. However, it is worth noting that DCM was used as a replacement for ethyl acetate in their recent publications [13,30]. This may be due to the inadequate extraction performance of ethyl acetate in their procedure, possibly resulting from the lack of the addition of a salt or ionic strength modifier (discussed in Section 3.1.2) [26].…”
Section: Ethyl Acetatementioning
confidence: 99%
“…Recently, aerobic granulation was introduced as an alternative to activated sludge process, 17 which is claimed to have a lower footprint than conventional approaches. Aerobic biodegradation has also been integrated with advanced oxidation processes to increase overall sulfolane removal efficacy 11,20 . In those integration treatment systems, aerobic biodegradation was used as a pre‐treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic biodegradation has also been integrated with advanced oxidation processes to increase overall sulfolane removal efficacy. 11,20 In those integration treatment systems, aerobic biodegradation was used as a pre-treatment process. Under aerobic environment, sulfolane can be degraded by microorganisms such as Variovorax paradoxus which has been isolated and identified from sulfolane-contaminated sites.…”
Section: Introductionmentioning
confidence: 99%